2020
DOI: 10.3928/01477447-20201023-01
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of COVID-19 on Orthopedic Practices and Surgeons in Louisiana

Abstract: This study was performed to analyze the effect that coronavirus 2019 (COVID-19) has had on orthopedic surgeons' practices, their patients, and orthopedic surgeons themselves through a survey distributed to members of the Louisiana Orthopaedic Association (LOA). An anonymous 22-question online survey was created and distributed to 323 LOA members. Of the 323 recipients of the survey, 99 (30.7%) responded. As a part of a multiple response set, in which respondents could choose more than one answer, the majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…Paul et al demonstrated the financial losses to orthopaedic surgeons, noting that the highest impacted states included Alabama, Georgia, and Missouri( 27 ). In a survey of Louisiana Orthopaedic Association members, Kale et al demonstrated that a majority of surgeons had applied for government assistance or took out loans during COVID-19 to support practice, personnel, and overhead costs( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Paul et al demonstrated the financial losses to orthopaedic surgeons, noting that the highest impacted states included Alabama, Georgia, and Missouri( 27 ). In a survey of Louisiana Orthopaedic Association members, Kale et al demonstrated that a majority of surgeons had applied for government assistance or took out loans during COVID-19 to support practice, personnel, and overhead costs( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ [21] , [22] , [23] , [24] ] Prior authors have documented up to 80% of US Orthopedic surgeons experiencing a decline in surgical volume following the onset of the pandemic. [ 25 ] Similarly, in Europe in April of 2020, it has been estimated that 92.6% of joint replacements were cancelled. [ 26 ] Again, the findings of the current study are consistent with prior reports, with both institutions having clear reductions in surgical volume and increases in wait times immediately following the onset of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been limited by examining disruptions in surgical care of people from single centres or regions and mainly related to cancers, 14 patient experiences, 15 and single routine or emergency procedures. 16-18…”
Section: Discussionmentioning
confidence: 99%